Modified-release hydrocortisone is associated with lower plasma renin activity in patients with salt-wasting congenital adrenal hyperplasia. Issue 1 (19th January 2023) - Tschaidse, Lea; Reisch, Nicole; Arlt, Wiebke; Brac de la Perriere, Aude; Linden Hirschberg, Angelica; Juul, Anders; Mallappa, Ashwini; Merke, Deborah P; Newell-Price, John D C; Perry, Colin G; Prete, Alessandro; Rees, D Aled; et al.
Abstract: Objective: Poorly controlled salt-wasting (SW) congenital adrenal hyperplasia (CAH) patients often require high 9α-fluorocortisol doses as they show high levels of 17-hydroxyprogesterone (17OHP), which is a mineralocorticoid (MC)-receptor antagonist. Design: We investigated the renin–angiotensin–aldosterone system in patients with SW-CAH receiving twice daily modified-release hydrocortisone (MR-HC, Efmody) compared with standard glucocorticoid (GC) therapy. Methods: Data were analyzed from the 6-month, phase 3 study of MR-HC ( n = 42) versus standard GC therapy ( n = 41). MC replacement therapy remained unchanged throughout the study. Blood pressure, serum potassium, serum sodium, plasma renin activity (PRA), and serum 17OHP and androstenedione concentrations were analyzed at baseline, 4, 12, and 24 weeks. Results: The median serum 17OHP in the morning was significantly lower on MR-HC compared with standard GC at 24 weeks (2.5 nmol L –1 (IQR 8.3) versus 10.5 nmol L –1 (IQR 55.2), P = .001). PRA decreased significantly from baseline to 24 weeks in patients on MR-HC (0.83 ng L –1  s –1 (IQR 1.0) to 0.48 ng L –1  s –1 (IQR 0.61), P = .012) but not in patients on standard GC (0.53 ng L –1  s –1 (IQR 0.66) to 0.52 ng L –1  s –1 (IQR 0.78), P = .613). Serum sodium concentrations increased from baseline to 24 weeks in patients on MR-HC (138.8 ± 1.9 mmol L –1 to 139.3 ± 1.8 mmol L –1, P = .047), but remained unchanged on standard GC (139.8 ± 1.6 mmol L –1 to 139.3 ± 1.9 mmol L –1, P = .135). No significant changes were seen in systolic and diastolic blood pressure and serum potassium levels. Conclusion: 6 months of MR-HC therapy decreased PRA and increased sodium levels indicating a greater agonist action of the 9α-fluorocortisol dose, which may be due to the decreased levels of the MC-receptor antagonist 17OHP.